Pengaruh Perubahan Diameter Lubang Saluran Keluar Jetmain dari 2,5 mm menjadi 2,8 mm pada Karburator terhadap Kinerja Mesin Bensin Empat Langkah Satu Silinder pada Sepeda Motor - Wardoyo Wardoyo; Andi Putro Sukendro (Jurnal Engine: Energi, Manufaktur, dan Material, 2017)
This study aimed to compare the influence of the hole diameter of the outlet of the main jet from 2.5 mm to 2.8 mm on the carburetor to the engine performance and fuel consumption.The test is performed with the brand gasoline motor honda tiger type GL 200 R  four-stroke single cylinder. The materials studied were the main jet. Tests performed with standard conditions in without making any changes. Testing machine at the ready on a dynamometers test bed. Then do the testing phase and retrieval of data that is torque and fuel consumption. Torque (Nm) play a modified jet yield increase of 2.2% from the main jet standard. Power (kW) jet modification produces a maximum power of around 2.2% of the main jet standard. The rate of fuel consumption (mf) on the main jet modification is greater than the main jet standard. Fuel consumption (sfc) on the main jet modification will further increase the standard of the main jet. Calorific fuel (Qi) in the main jet modification is greater than the main jet standard. Jet played modifications that do not significantly change the main jet standard.